2011
DOI: 10.2182/cjot.2011.78.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Brain Injury from a First Nations' Perspective: Teachings from Elders and Traditional Healers

Abstract: Funding is required for traditional healing services to provide culturallysafe and responsive occupational therapy services to First Nations individuals with brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Comparable to findings by Elder 30 , elders and traditional healers participating in the study by Keightley, et al 52 identified that spiritual healing -which can only be understood by traditional methods -is paramount towards the healing process. Keightley, et al 52 also found that healing and treatment is a process of western medicine and traditional methods working together. For example, western medicine was identified as important towards understanding how to treat and detect brain injury, while traditional methods can be useful for providing guidance and motivation for community members who have experienced brain injury.…”
Section: Tbi Rehabilitation Outcomesmentioning
confidence: 67%
See 1 more Smart Citation
“…Comparable to findings by Elder 30 , elders and traditional healers participating in the study by Keightley, et al 52 identified that spiritual healing -which can only be understood by traditional methods -is paramount towards the healing process. Keightley, et al 52 also found that healing and treatment is a process of western medicine and traditional methods working together. For example, western medicine was identified as important towards understanding how to treat and detect brain injury, while traditional methods can be useful for providing guidance and motivation for community members who have experienced brain injury.…”
Section: Tbi Rehabilitation Outcomesmentioning
confidence: 67%
“…A single study 52 -which did not entirely meet the review criteria due to a focus on brain injury and not TBI -provided findings regarding Indigenous perspectives to treatment for brain injury. Keightley, et al 52 investigated First Nations perspectives concerning brain injury healing and rehabilitation in Canada.…”
Section: Tbi Rehabilitation Outcomesmentioning
confidence: 99%
“…Despite the dearth of literature exploring the intersection of TBI and IPV, some comparisons can be made with the few studies to explore either TBI or IPV within an Indigenous context in Canada, where themes such as challenges to post-injury care, issues of cultural competency, and need for education and screening were also present. Studies examining post-injury transition back to community living report that TBI survivors from Canadian First Nations have a more difficult time than those from settler populations (Keightley et al, 2009;Keightley et al, 2011a). Many of the emergent themes discussed here reflect challenges with existing services, such that women are also likely to experience lower success rates with community reintegration post-injury.…”
Section: Discussionmentioning
confidence: 92%
“…Consultations with First Nations elders and traditional healers identified the importance of spirituality, conflicting notions of fixing illness or injury versus living with wellness, working collaboratively in addressing brain injury, and the need for financial support for traditional healing as important in providing culturally safe and responsive services. These studies, however, did not explicitly address brain injury in the IPV context (Keightley et al, 2011a(Keightley et al, , 2011b. Given the challenges of supporting TBI among Indigenous populations in Canada, the elevated rates of violence and injury experienced by women exposed to IPV and the increased level of physical assault among Indigenous women in Canada, it is important to understand the unique context and service needs of these diverse, and distinct, groups of women.…”
Section: Introductionmentioning
confidence: 99%
“…Interviews with traditional healers identified culturally specific barriers and facilitators for treating AI/AN patients at a level I trauma center, suggesting a need for improved cultural competence among providers caring for AI/AN patients with traumatic injury [10]. A study of Canadian First Nations elders found differences between the Western and traditional approach to healing after TBI, and stressed the need for culturally safe and responsive occupational therapy services for First Nations individuals with TBI [11]. These studies suggest that the worldview of AI/AN people regarding TBI and cultural expectations for service differs from that of the majority population, which may affect rehabilitation outcomes for AI/AN children with TBI.…”
Section: Introductionmentioning
confidence: 99%